Faktor-Faktor yang Mempengaruhi Ketepatan Waktu Penyampaian Laporan Keuangan Pada Perusahaan Manufaktur Tekstil dan Garment di Bursa Efek Indonesia Periode 2013-2017 - Hanifah Nuraini Hadiesti (AKUNTANSI DEWANTARA, 2020)
The purpose of this research is to analyze the effect of profitability, company size, and leverage. The population in this study is a textile and garment manufacturing company totaling 18 (eighteen) companies. The sampling method used in this study was purposive sampling, so as to get 9 (nine) sample companies. This study uses secondary data types to get information about all the variables in this study that are on the Indonesia Stock Exchange. This study uses accounting analysis, descriptive statistics, and also logistic regression tests. The results showed that the profitability has positive effect on the timeliness of financial reporting, while company size and leverage didn’t have effect on timeliness of financial reporting.